Central American Enunciations from US Zones of Indifference, or the Sentences of Coloniality - Oriel María Siu (Studies in 20th & 21st Century Literature, 2013)
This essay explores Central American diasporic experiences in the US as sites for the continued exertion and reproduction of coloniality. A longstanding matrix of power transgressing all forms of borders and permeating all aspects of life—an irreversible and transgressive disease—coloniality operates so forcefully that it upholds its own survival. In the process, we live its plural incongruity and even extend its most contemptuous signs. Surveying a series of narrative texts produced from within the Central American diaspora in cities like Los Angeles and New York—Roberto Quesada’s Big Banana, Oscar René Benitez’s Inmortales, Hector Tobar’s Tattooed Soldier, and Mario Bencastro’s Odyssey to the North—this article examines the diverse ways through which the diasporic subject experiences coloniality, and how this subject unquestioningly contributes to its endurance.
Keywords: diaspora; Central America; Central American; colonialism; colonality; US